Iron-enriched mycelia of edible and medicinal basidiomycetes - Meniqueti, Adriano Borges (Environmental technology, 2022)
Iron bioaccumulation in basidiomycetes is an alternative to recover ferrous sulphate from titanium dioxide pigment production and to produce an iron-enriched mycelial biomass. This study aimed to evaluate iron bioaccumulation capacity in vegetative mycelium of edible and medicinal fungi grown in malt extract liquid medium with different ferrous sulphate contents. Five basidiomycetes were grown in malt extract liquid medium with different iron contents from 0.116 to 100 mg L-1 iron. The iron content of dried mycelial biomass bioaccumulated with iron was determined by flame atomic absorption spectrophotometry. All fungi grew on the iron culture media and the mycelial biomass growth ranged from 3.24 ± 0.65a mg mL-1 to 12.46 ± 0.29 mg mL-1. Iron addition to culture media increased the iron content in the mycelial biomass from 4000-13,000-fold compared with control. Pleurotus ostreatus (2181 ± 218 mg kg-1) presented the greatest iron content in the mycelial biomass, followed by Schizophyllum commune (1769 ± 131 mg kg-1), Agaricus subrufescens (1272 ± 8.84 mg kg-1), and Ganoderma lucidum (840 ± 75 mg kg-1). P. ostreatus, followed by S. commune, and G. lucidum at 90 and 100 mg L-1 iron in the culture medium are the best choices to produce iron-enriched mycelial biomass. This extensive study of several edible and medicinal basidiomycetes grown in different iron contents was effective in recovering ferrous sulphate byproduct and transferring it to mycelium to produce a new nutraceutical food of iron-enriched mycelial biomass